Functional aspects of protein kinase C FRET probe performance - Jost, Christiane (2006)
Understanding cellular signaling pathways and their cross talk increasingly depends on the visualization of their spatio-temporal dynamics. This thesis investigates different factors influencing the performance of two FRET based protein kinase C (PKC) probes, KCP-1 and KCP-2. KCP-1 consists of the truncated PKC substrate pleckstrin, sandwiched between two fluorescent proteins, EYFP and GFP2. KCP-2 is a shortened version of KCP-1, missing the last 18 amino acids of the pleckstrin insert (the acidic loop). The EYFP/GFP2 emission ratio of KCP-1 increases upon phosphorylation, while it decreases in KCP-2. Both probes are reversible. We examined the influence of linker length, charge distribution in particular domains of the probe, and fluorophore dimerization on probe performance. Different FRET pairs, including novel fluorescent proteins and novel labeling techniques, were tested in an effort to vary and optimize the spectral properties of KCP probes. Both probes, KCP-1 and KCP-2, were shown to be sensitive to elongation in their N-terminal linker region. The signal amplitude of the probe was diminished with increasing linker length. Shortening of the same linker region reduced probe performance, although not to the same extent as elongation. This demonstrated the importance of linker length for proper orientation of the fluorophores in the probe molecule. Any changes in the N-terminal PH domain of the pleckstrin insert, for example shortening or replacing basic amino acids with uncharged or acidic residues, had severe impact on probe performance. The direction of the KCP-1 signal was reversed, showing a decrease instead of an increase after phosphorylation. The reversal of signal in KCP-1 probes reflects that specific interactions between the PH domain and the acidic loop are crucial for probe performance. In KCP-2, the impact was less striking, although the signal was reduced. Abolishing the fluorescent proteins' ability to dimerize, led to strongly reduced KCP-2-like signals in both probes. This is the first time that fluorophore dimerization was shown to be essential for the mechanism of action of a genetically encoded sensor. Based on this data, we propose the following models for the mechanism of these PKC probes: In unphosphorylated KCP-2, dimerization of fluorophores serves as a clamp, pulling the two fluorophores together to a closed, quasi cyclized conformation. Phosphorylation of the probe leads to a more open conformation, increasing the average distance between the two fluorophores. This results in a decrease of FRET efficiency after phosphorylation. Two interactions determine the mechanism in KCP-1. Again, the dimerization of the two fluorophores serves as a clamp, pulling the fluorophores to close proximity. An additional interaction between the PH domain and the acidic loop changes the relative orientation of the transition dipole moments in the probe, resulting in a decreased initial FRET efficiency, compared to KCP-2. Phosphorylation of the probe imposes a strain on the intramolecular architecture that rearranges the transition dipoles, leading to an increase in FRET efficiency. The need for a molecular clamp, dimerization of fluorescent proteins in KCP-1 and KCP-2 probes, within the molecule explains why probes containing new monomeric fluorescent proteins or other labels based on full sized proteins did not yield functional sensors. Using the small fluorophore FlAsH, however, we were able to create a smaller sized PKC probe. This probe will allow NMR experiments and structural analysis of a FRET probe for the first time.
Keywords: Hochschulschrift